EGOISME SEKTORAL & KEDAERAHAN SEBAGAI TANTANGAN PROGRAM PEMBANGUNAN BERKELANJUTAN (Kasus Pengelolaan & Pemanfaatan Sumber Air Senjaya di Perbatasan Wilayah Kabupaten Semarang dengan Kota Salatiga) - Mardimin, Johanes (KRITIS, 2016)
Indonesian Otonomi Daerah or Desentralization policy had been dilemmatic and problematic when social control of society and supra-structure of the local government (supra-district) are weak and not effective. Beside exploitative and corruptive, that policy tend to stimulated sectoral egoism and regional (district) egoism. This paper which discuss the utilization and management of Senjaya water resources is a case that expose the sectoral egoism and regional egoism at the political decision making at the district level as the spirit of unsustainable development.Kata Kunci: Otonomi Derah, egoisme sektoral &, kedaerahan, keberlanjutan